Characterization of Ag nanoparticles biosynthesized by Bacillus sp. HAI4 in different conditions and their antibacterial effects - Mojtaba Taran, Maryam Rad, Mehran Alavi (Journal of Applied Pharmaceutical Science, 2016)
In the present study, Ag nanoparticles (NPs) were synthesized by eco-friendly method. Design and analysis of Taguchi experiments was done by the Qualitek-4 software. Effect of AgNO3 concentration (0.1, 0.01 and 0.001 M), incubation and culturing time (48, 72, 96 hours) as three different levels were measured in NPs biosynthesis. We carried out biosynthesis of NPs through cell-free culture supernatant of Bacillus sp. HAI4. X-ray diffraction (XRD), Fourier Transform Infra-Red spectroscopy (FT-IR), Ultraviolet–Visible spectroscopy (UV) and Field Emission Scanning Electron Microscope (FESEM) techniques were applied for NP characterization. Results of Taguchi analysis showed optimum condition with 12.641% amount which is good result of biosynthesis by this bacterium. XRD analysis proved the crystalline and amorphous nature of synthesized silver NPs. Analysis of FESEM demonstrated that Ag nanoparticles were formed as spherical shapes with size of 33/264 nm. Also, for evaluating of antibacterial effects, maximum zone of inhibition, two important multidrug resistant pathogenesis bacteria, Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 43300 were used. Three levels of Ag NPs concentrations had antibacterial effect on these bacteria (1, 1 and 0.5 cm for E.coli and 1, 1.1 and 1.1cm for S.aureus), but there was no significant difference between three levels.
Keywords: Ag nanoparticles, Bacillus sp. HAI4, Qualitek-4 software, UV spectroscopy, SEM, Staphylococcus aureus.